NCDs - Clare Herrick (Medicine Anthropology Theory, 2019)
The global burden of mortality and morbidity attributable to noncommunicable diseases (NCDs) now exceeds that of infectious disease. Yet, concern is mounting that global political prioritisation and action have stalled. The failure of NCDs to capture public and political imaginations has been ascribed to a number of reasons, with some recently contending that the very name of the disease classification is to blame. In this piece, I reflect critically on why discourse about NCDs has not compelled global action proportionate to the magnitude of the suffering these diseases cause. Failure to act on NCDs, I argue, is not a failure of terminology alone.